Hubungan Tingkat Pengetahuan Terhadap Sikap Remaja Tentang Pencegahan Kanker Serviks di SMAN 10 Semarang - Nabila Cahyaning Tyas; Tutik Rahayu; Sri Wahyuni (Journal of Medical Practice and Research, 2026)
Cervical cancer remains a significant public health concern among women, and preventive efforts through early education are essential, particularly among adolescents. This study aimed to analyze the relationship between the level of knowledge and adolescents’ attitudes toward cervical cancer prevention at SMAN 10 Semarang. A quantitative analytic design with a cross-sectional approach was employed, involving 113 female students selected using total sampling techniques. Data were collected using structured questionnaires measuring knowledge and attitudes, and analyzed using the Chi-Square test. The results indicated that most respondents had a good level of knowledge and positive attitudes toward cervical cancer prevention. Statistical analysis revealed a significant relationship between knowledge level and attitude (p < 0.05), indicating that higher knowledge is associated with more positive attitudes. The findings suggest that knowledge plays a critical role as a cognitive determinant influencing affective responses toward preventive behavior. Strengthening reproductive health literacy through structured educational interventions in schools is recommended to enhance adolescents’ readiness and commitment to cervical cancer prevention